2005
DOI: 10.1001/archderm.141.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Ribosomal RNA of Mycobacterium tuberculosis Complex in Sarcoidosis

Abstract: To determine whether Mycobacterium tuberculosis ribosomal RNA (rRNA) is present in fresh tissue specimens from patients with sarcoidosis. Design: A prospective study. Setting: A university-based hospital. Patients: Thirty-five patients diagnosed as having sarcoidosis at the University Hospital of Bellvitge, Barcelona, Spain, were included in the study. Fresh tissue samples with granulomatous inflammation were prospectively collected between 1997 and 2001 from all patients. For each sample tested, approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Both Mycobacterium tuberculosis complex (MTBC) and nontuberculous mycobacteria (NTM) were investigated in most of the 36 relevant studies, although some used primers to detect only M. tuberculosis [26, 28–33, 38, 39, 41, 42, 51, 52, 55], and others detected only nontuberculous mycobacteria [44, 50]. …”
Section: Resultsmentioning
confidence: 99%
“…Both Mycobacterium tuberculosis complex (MTBC) and nontuberculous mycobacteria (NTM) were investigated in most of the 36 relevant studies, although some used primers to detect only M. tuberculosis [26, 28–33, 38, 39, 41, 42, 51, 52, 55], and others detected only nontuberculous mycobacteria [44, 50]. …”
Section: Resultsmentioning
confidence: 99%
“…123,124 The term 'immune restoration disease' has been used for this circumstance. 133 Based on these results the authors concluded that this organism cannot be considered as the etiological agent of the disease. 125 The etiology of sarcoidosis remains controversial although an infectious origin has long been suspected.…”
Section: Introductionmentioning
confidence: 99%
“…As an example of arguments in favor of a possible role for M. tuberculosis, it has been found that the enzyme catalase-peroxidase (mKatG) is not only found in tissues affected by sarcoidosis, but is also a target of the immune response in patients with sarcoidosis [23].However, previous studies attempting to detect mycobacterial nucleic acids in lesions of sarcoidosis have been controversial [22,24].…”
Section: Triggering Factorsmentioning
confidence: 99%
“…Confirmation of diagnosis is done by histopathology. Skin offers advantages compared to other affected organs since it is easily accessible [24].…”
Section: Epidemiology Differential Diagnosis Regional and Ethnic Vamentioning
confidence: 99%